Impact of weekly training-load structure and content on the risk of injury in professional Rugby Union match-play - Chéradame, J.; Loursac, R.; Piscione, J.; Carling, C.; Decq, P.; Jacqmin-Gadda, H. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to investigate the impact of different components of daily training load during the week preceding the match on the risk of sustaining a match injury in professional rugby union. A cohort of 72 players from a single professional French club participated. Global positioning system-derived data including total distance (TD) and high-speed distance in addition to ratings of perceived effort (RPE) for both on- and off-pitch (gym-based strength conditioning work) training were collected for each training session over 3 seasons (2017-2020). The association between the daily measures of external and internal training load over the week preceding the day of the match (MD) and the subsequent risk of injury in match-play was estimated using a mixed-effects logistic model adjusted for contextual and individual factors. A total of 184 injuries were sustained in 128 matches (incidence: 81.2 injuries per 1,000 player hours). Higher RPE values for the strength conditioning session on MD-5 (p < 0.001) and for the on-pitch session on MD-1 (p = 0.04) were associated with an increased risk of injury in matches. On MD-2, a higher TD covered and that run at high speed (>MAS) were, respectively, associated with a higher (p = 0.03) and lower risk (p = 0.02) of injury in matches played. This study in professional rugby union shows that different components of external and internal load had varying influences on injury risk and particularly in relation to the day on which these were performed in the week leading up to the next match. At MD-2, training load favoring intensity rather than volume could reduce the risk of match-play injury.